Fundamentals of roman private law - Mousourakis, George (Springer Berlin Heidelberg, 2012)
Roman law forms a vital part of the intellectual background of many legal systems currently in force in Continental Europe, Latin America, East Asia and other parts of the world. Knowledge of Roman law, therefore, constitutes an essential component of a sound legal education as well as the education of the student of history. This book begins with a historical introduction, which traces the evolution of Roman law from the earliest period of Roman history up to and including Justinian's codification in the sixth century AD. Then follows an exposition of the principal institutions of Roman private law: the body of rules and principles relating to individuals in Roman society and regulating their personal and proprietary relationships. In this part of the book special attention is given to the Roman law of things, which forged the foundations for much of the modern law of property and obligations in European legal systems. Combining a law specialist's informed perspective with a historical and cultural focus, the book provides an accessible source of reference for students and researchers in many diverse fields of legal and historical learning.